Proposed novel multiphase-multilevel inverter configuration for open-end winding loads - Padmanaban, Sanjeevikumar; Wheeler, Patrick; Blaabjerg, Frede; Ertas, Ahmet H.; Ojo Olorunfemi, Joseph; Szcześniak, Pawel (2016)
This article address a new multiphase-multilevel inverter configuration for open-winding loads and suitable for medium power (low-voltage/high-current) applications such as ‘More Electric Aircraft’. Modular structure comprised of standard dual three-phase voltage source inverter (VSI) along with one additional bi-directional semi-conductor device (MOSFET/IGBT) per phase and two capacitors with neutral point. The additional switches and capacitors are introduced to generate the additional voltage levels in outputs of the VSI. An original modified single carrier five-level modulation (MSCFM) algorithm is developed in this work and overcomes the complexity of standard space vector modulations, easy for real implementation purposes in digital processors. Proposed six-phase multilevel inverter configuration generates multilevel outputs with benefit in comprises with standard multilevel inverter topologies. Further, the complete numerical model of the proposed AC converter along with pulse-width modulation (PWM) is developed with Matlab/PLECS simulation software’s. A set of observed results is presented in balanced working condition and always shown good agreement with the theoretical developments.